Do Government Policies Foster Environmental Performance Of Enterprises From CEE Region? - Lewandowska, Małgorzata Stefania (Comparative Economic Research. Central and Eastern Europe, 2016)
In recent years, EU countries, including these from the Central Eastern European (CEE) region has recognised, that eco-innovation should be treated as strategic priority of their economies. The aim of this paper is to present a cross-country analysis of the connection between eco-innovation and its main drivers within firms from selected CEE countries (Bulgaria, Czech Republic, Romania) and Germany. The empirical part is based on micro-data for Community Innovation Survey (CIS) 2006–2008. Based on the results of stepwise regression between main policy actions sustaining innovation activity and eco-innovation performance we can conclude, that financial support for innovation activities has a rather limited role in promoting eco-innovation. At the same time enterprises from the CEE region regard environmental regulations as the most important drivers of eco-innovation. In Germany, a country ranked in the highest category in the Eco-Innovation Scoreboard, the variety of forces that influence eco-innovation is much more wide-ranging. This indicates that government actions should take a broader look and lay the more general bases fostering the model of a green growth.